The effectiveness of cognitive-behavioral therapy on the resilience of soldiers with suicidal ideation - younes kakavand; sajad Panahifar (علوم و فنون نظامی)
One of the most important causes of death in societies is the issue of suicide, which has become a serious issue for the public health.The significance of investigating suicide and its destructive effects on the structure of the society has prompted societies to take effective measures with the help of experts to protect the mental health of the peopleThe present study was conducted with the aim of investigating effectiveness of cognitive-behavioral therapy on the level of resilience of soldiers with suicidal thoughts.The research method was semi-experimental with a per-test post-test design with a control group.Using the purposeful sampling method, 30 soldiers with suicidal thoughts (based on the cutting line of the Beck suicidal Ideation Scale) were selected from one of the barracks and randomly divided into two experimental (15 people) and control groups (15 people) in Tehran in 2022; first, the pre-test was conducted on the entire sample population; then cognitive-behavioral therapy training was conducted for the experimental group for 12 sessions of 60 minutes each session, and the control group did not receive any treatment. After these steps, the post-test was performed. In this research, the resilience questionnaire of Connor and Davidson (2003) was used and the obtained data were analyzed by the analysis of covariance method.The results indicated the effectiveness of cognitive-behavioral therapy on resilience (P=0.001, F=347.532, ETA=.686) soldiers with suicidal thoughts.The research findings showed that cognitive-behavioral therapy training cab be effective in barracks environment for soldiers and can also be effective in enhancing resilience and cognitive factors